Avant-Garde Blake: From Francis Bacon To Oz Magazine. Issue 1 (31st May 2022) - Hopkins, David
Abstract : This article discusses how we might formulate an account of William Blake's avant-garde reception. Having dealt with Peter Bürger's theorisation of the notion of 'avant-garde', it concentrates on a series of portraits, made from Blake's life mask, by Francis Bacon in 1955. This 'high art' response to the Romantic poet is then contrasted with a series of 'subcultural' responses made from within the British counterculture of the 1960s. Case studies are presented from the alternative magazine production of the period (notably an illustration from Oz magazine in which Blake's imagery is conflated with that of Max Ernst). An article by David Widgery in Oz on Adrian Mitchell's play Tyger (1971) is also discussed to show how the scholarly literature on Blake of the period (mainly David Erdman) was called on by the counterculture to comment on political issues (e.g. Enoch Powell's 1968 'Rivers of Blood' speech). The final section of the article shows how the 'avant-gardism' of Oz 's utilisation of Blake might be counterposed to the more activist left-wing approach to the poet in small magazines such as King Mob with their links to French situationism. In terms of the classic avant-garde call for a reintegration of art and life-praxis, such gestures testify to a moment in the 1960s when Blake may be considered fully 'avant-garde'.